P11.04.A Observational, prospective multicenter study on the role of body mass index (BMI) in the development of thrombotic complications in cancer patients with PICC: preliminary results. (5th September 2022) - Simonetti, G; Gammone, M; Bersani, A; Garofalo, R; Anghileri, E; Botturi, A; Gaviani, P; Redaelli, V; Silvani, A
Abstract: Background: Peripherally inserted central catheters (PICC) became widespread and changed substantially the approach to the patients venous system. They guarantee, both in hospital and at home, a stable and safe vascular access to administer irritants or vesicants therapies. However, the benefit provided may occasionally be affected by relevant thrombotic complications especially in patients with hypercoagulability such as oncological patients. Among the identification of independent risk factors, the role of a BMI>25 kg/m2 is now emerging in literature with conflicting results. Material and Methods: Oncological patients with PICC were included in this multicenter prospective study. We evaluated clinical data, BMI, KPS, steroid therapies and anticoagulants at the time of PICC positioning and at regular intervals. Results: A total of 51 patients were analyzed. The median KPS was 90 (range 80-100), and the median ECOG was 1 (range 0-3). The most common tumors were represented by: lymphomas both Hodgkin and non-Hodgkin (38%), lymphatic and myeloid leukemia (35%), neurooncological tumors including glioblastoma, primary central nervous system lymphoma, anaplastic astrocytoma and meningioma (15%), other solid cancer (breast, gastroesophageal, rectal cancer) (12%).55% patients were at first diagnoses, 12% were at the first recurrence, and the remaining were at the second or third recurrence. No malpositioning were registered. 18% of patients were on anticoagulant/antiplatelet therapy, 67% were treated with steroids. Concerning BMI, 39% was normal weight, 43% overweight and 10% obese, only 2% was considered underweight. Overall, 8% of patients developed PICC related thrombosis within a median time of 68 days (49-87) after PICC implantation mainly occurred in upper right extremity insertion sites. We therefore assessed the incidence of PICC related thromboembolic events in the groups, with 4% of event registered in the cohort of patients overweight/obese, and 14% of events in the cohort of patients with normal weight/underweight. Conclusion: Preliminary analysis does not allow to draw firm conclusions. It will therefore be necessary to reach the sample size for achieve generalizable results and confirm the risk of developing thromboembolic events in overweight/obese patients. Meanwhile, an accurate anamnesis and a physical evaluation with particular attention to the presence of malnutrition, both over nutrition and undernutrition, could help to identify potential oncological patients at risk of developing PICC related thrombosis.